2016
DOI: 10.1259/bjr.20150920
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations and pre-operative imaging technique concerning the anterolateral thigh flap: guiding the surgeon

Abstract: The anterolateral thigh (ALT) flap has widespread use throughout the body because of the many engineering options. The ALT has a complex local vasculature, which can be of importance for the surgical approach. In general, the flap receives its perfusion from branches of the lateral circumflex femoral artery (LCFA). The LCFA, however, has a large anatomic variance. CT angiography can guide the surgeon in the selection of the most suitable site and aid in the surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
(8 reference statements)
0
16
0
2
Order By: Relevance
“…For this reason, preoperative CTA is frequently an essential part of the preoperative assessment in many reconstructive settings (e.g., lower extremity trauma), especially since most literature reports higher rates of insufficient vasculature, up to 16% (►Table 6). [26][27][28] Excluding that one instance (which was excluded from analysis), all of our patients' studies (58 of 59 or 98.3%) had suitable perforators on CTA. It is possible that because many of our patients were relatively healthy and undergoing nontrauma related reconstructions (i.e., transgender men undergoing phalloplasty), that there were less perturbations to normal vascular anatomy than are present in most other studies.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, preoperative CTA is frequently an essential part of the preoperative assessment in many reconstructive settings (e.g., lower extremity trauma), especially since most literature reports higher rates of insufficient vasculature, up to 16% (►Table 6). [26][27][28] Excluding that one instance (which was excluded from analysis), all of our patients' studies (58 of 59 or 98.3%) had suitable perforators on CTA. It is possible that because many of our patients were relatively healthy and undergoing nontrauma related reconstructions (i.e., transgender men undergoing phalloplasty), that there were less perturbations to normal vascular anatomy than are present in most other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical studies have reported the presence of an oblique branch in the ALT flap in only 34% of cases 9,12 ; therefore, a branch-based chimeric ALT flap cannot be definitely dissected in a specific patient. A preoperative study of the anatomy of the LCFA using ultrasound or other imaging techniques should be performed to help design the flap 13,14 . Alternative surgical plans should be made preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…ALT flap technique also showed some limitations. The anatomic variations of this surgical area, including complete absence of identifiable perforators and bulky oral component, especially female patients, which thereby make it not the best-practice ( 18 , 19 ). In this present study, the thickness of subcutaneous fat was nearly up to 50 millimeters in one of patient’s thigh (Fig.…”
Section: Discussionmentioning
confidence: 99%